Study on Removing Methanthiol with Chlorine Dioxide - Liang, Dongsong; Lin, Jizhen; Song, Xueping (Asian Journal of Chemistry, 2014)
In this paper, the experimental device of chlorine dioxide (ClO2) solution removing methanthiol (CH3SH) gas was designed and the removal process was studied. The absorbent of residual ClO2, the amount of ClO2, the reaction temperature, the pH value of ClO2 solution and the air flow effect on the removal rate of CH3SH were studied. The optimum conditions of removing CH3SH are as follows: the mixed lye of NaOH and Na2S as the absorbent of residual ClO2 and the molar ratio of NaOH and Na2S 1:1, the molar ratio of CH3SH and ClO2 1:2.5, the temperature 35 °C, the pH value of ClO2 solution 2, the compressed air flow 0.75 m3/h. Under this conditions, the results show that the concentration of CH3SH is reduced from the initial 1.457 g/m3 to 0.032 mg/m3, the removal rate of CH3SH attains to 99.8 %, which meets level 3 national emission standards.